Digital interventions for problematic cannabis users in non-clinical settings: findings from a systematic review and meta-analysis - Hoch, Eva (European addiction research, 2016)
Background: Existing cannabis treatment programs reach only a very limited proportion of people with cannabis-related problems. The aim of this systematic review and meta-analysis was to assess the effectiveness of digital interventions applied outside the health care system in reducing problematic cannabis use. Methods: We systematically searched the Cochrane Central Register of Controlled Trials (2015), PubMed (2009-2015), Medline (2009-2015), Google Scholar (2015) and article reference lists for potentially eligible studies. Randomized controlled trials examining the effects of internet- or computer-based interventions were assessed. Study effects were estimated by calculating effect sizes (ESs) using Cohen's d and Hedges' g bias-corrected ES. The primary outcome assessed was self-reported cannabis use, measured by a questionnaire. Results: Fifty-two studies were identified. Four studies (including 1,928 participants) met inclusion criteria. They combined brief motivational interventions and cognitive behavioral therapy delivered online. All studies were of good quality. The pooled mean difference (Δ = 4.07) and overall ES (0.11) give evidence of small effects at 3-month follow-up in favor of digital interventions Conclusions: Digital interventions can help to successfully reduce problematic cannabis use outside clinical settings. They have some potential to overcome treatment barriers and increase accessibility for at-risk cannabis users.
Gesehen am 22.10.2019